RELIGIOUS CULTURE through PRAYING HABIT-FORMING MANAGEMENT before LEARNING - Sofiandi Sofiandi (Madania: Jurnal Ilmu-Ilmu Keislaman, 2016)
The term ”Religious Culture” in this journal has the same meaning with religious atmosphere. The importance of prayer as a form of supplication toward the Almighty, however, can  be  such an auto-suggestion for every students to boost  and generate their spirit in persuing kowledge. God's command to start everything by calling on His name and praying by asking for His help, guidance as well as His mercy is a command that implies one will not be left alone in facing all his problems, but in fact, there will always be intercession of God. Should we hope, through this habit, all daily activities of teaching and learning be considered by Allah the Almighty as  good deeds where we can be classified as the people of those who always perform dhikr (remembrance) to Him